BARRIERS IN THE IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT IN INDONESIAN MANUFACTURING ORGANIZATIONS - Kifayah Amar; Zuraidah Mohd Zain (Institute of Research and Community Outreach - Petra Christian University, 2001)
This study examines the barriers faced by Indonesian manufacturing organizations in the implementation of TQM. Out of a total sample size of 364 selected organizations identified for a multi-response survey, 78 organizations responded. The analysis identified 11 pertinent factors acting as barriers that are most frequently faced by the local organizations. These are issues related to human resource, management, attitude towards quality, organizational culture, interdepartmental relation, material, machine and equipment, information, method and training.